2020
DOI: 10.18632/aging.103053
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-induced glucolipotoxicity impairs wound healing ability of adipose-derived stem cells-through the miR-1248/CITED2/HIF-1α pathway

Abstract: Despite being an attractive cell type for mesenchymal stem cell (MSC) transplantation therapy for wound healing, human adipose-derived stem cells (hADSCs) from diabetes mellitus (DM) patients result in remarkable retention of stem cell activity due to diabetes-induced glucolipotoxicity. We explored the effect of diabetes and medium containing AGEs on the cell activity, phenotype, multipotency, angiogenic potential, and the therapeutic effect of hADSCs. Then, miRNA-1248 was selected by miRNA microarray analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…Moreover, the expression of miRNA-1248 was reduced, paralleled by increased expression of CBP/p300-interacting transactivator with ED-rich tail 2 (CITED2), an inhibitor of HIF-1α, which influences growth factors that promote cellular proliferation, angiogenesis, and wound healing. Thus, the authors of the study concluded that glucolipotoxicity impaired the effectiveness of AMSCs through the miR-1248/CITED2/HIF-1α pathway (Xiao et al, 2020). As previously mentioned, several studies have shown that hyperglycemia reduces the osteogenic potential of MSCs.…”
Section: Micrornas and Lncrnasmentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, the expression of miRNA-1248 was reduced, paralleled by increased expression of CBP/p300-interacting transactivator with ED-rich tail 2 (CITED2), an inhibitor of HIF-1α, which influences growth factors that promote cellular proliferation, angiogenesis, and wound healing. Thus, the authors of the study concluded that glucolipotoxicity impaired the effectiveness of AMSCs through the miR-1248/CITED2/HIF-1α pathway (Xiao et al, 2020). As previously mentioned, several studies have shown that hyperglycemia reduces the osteogenic potential of MSCs.…”
Section: Micrornas and Lncrnasmentioning
confidence: 84%
“…In addition to the above features, MSCs in hyperglycemic conditions show decreased immunomodulatory properties (Montanucci et al, 2016), angiogenesis (Xiao et al, 2020), and migration (Liu Y. et al, 2020), but increased SASP and insulin resistance. SASP is mainly composed of various extracellular growth factors, cytokines/chemokines and receptor antagonists.…”
Section: Other (Sasp Immunomodulatorymentioning
confidence: 99%
“…However, cells were almost excluded except for ADSCs after in vitro cell culture. In our previous studies, we found that the percentage of MSC-specific cell markers (CD90 + , CD73 + , or CD105 + ) in cultured SVF cells were more than 95%, while the percentage of hematopoietic-specific cell markers (CD34 -, CD11b -, CD19 -, or CD45 -) was negative [30][31][32]. In this study, CMs were collected from the medium of ECM/SVF and SVF after cultured for 48 h. Therefore, we consider that the biological efficacy of CMs mainly attributed to ADSCs.…”
Section: Discussionmentioning
confidence: 96%
“…Through the degradation of SP neurons, IPFP-ASCs could be used to manage pain and work in multiple ways to decrease inflammation. Previous literature suggests that obesity and type II diabetes mellitus alter ASC therapeutic properties; however, there are no studies as of yet that have investigated if these changes are found in IPFP-ASCs [ 49 , 50 ]. Therefore, IPFP-ASCs will be used to engineer adipose tissue for the knee-specific MPS.…”
Section: Discussionmentioning
confidence: 99%